2020
DOI: 10.1007/s42452-020-2746-8
|View full text |Cite
|
Sign up to set email alerts
|

A natural tropical freshwater wetland is a better climate change mitigation option through soil organic carbon storage compared to a rice paddy wetland

Abstract: The high productivity together with hypoxic conditions in sediments enables wetlands to accumulate large amounts of soil organic carbon (SOC). However, natural tropical freshwater wetlands are increasingly being converted into other land uses, mainly rice cultivation. In this study, we investigated the impact of conversion of a natural tropical freshwater wetland into a rice paddy wetland on SOC, by determining SOC content, density and storage potential in the natural section (under different vegetation commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
(120 reference statements)
1
3
0
Order By: Relevance
“…Similar results were obtained by other authors [29,30,128,129]. The degradation of wetlands, especially for agriculture [123] was driven by land shortage and the growing demand for food and income from an ever-growing population. Therefore, to protect the lake from further deterioration of water quality, there is need to manage LU activities in the catchment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were obtained by other authors [29,30,128,129]. The degradation of wetlands, especially for agriculture [123] was driven by land shortage and the growing demand for food and income from an ever-growing population. Therefore, to protect the lake from further deterioration of water quality, there is need to manage LU activities in the catchment.…”
Section: Discussionsupporting
confidence: 88%
“…Lake Kyoga and its catchment wetlands, in the 1980s used to have a dense network of natural vegetation with Miscanthidium spp, papyrus, and Typha, being the primary vegetation [71], and the lake had good water quality. Since the increased conversion of wetlands areas into mainly rice fields [118], an economic activity which cannot sequestrate nutrients like the natural vegetation [121][122][123], loading of nutrients into the lake has continued. This was indicated by the increase in the concentrations of nutrients, sediments and chl-a over the study period (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…This relationship has been observed in similar field wetlands and ponds, with the larger surface area of finer particles allowing greater potential for binding of organic matter (Cooper et al, 2019; Ockenden et al, 2014). The generally higher OC and lower bulk density of sediment in online features may in part be explained by a more extensive cover of wetland vegetation, leading to greater carbon inputs into the waterlogged hypoxic or anoxic sediment (Were et al, 2020). A study of sediment in small natural ponds in Northumberland found a similar pattern, with the highest OC (up to 15%) in permanent, vegetated ponds and the lowest in temporary ponds with little vegetation (Gilbert et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These unique characteristics have a great influence on carbon and nitrogen cycling in these ecosystems (Mitsch et al 2013). Several studies have acknowledged that conversion of natural wetlands into farmed wetlands compromises climate change mitigation by enhancing carbon and nitrogen emission (Owino et al 2020;Were et al 2020b;Ajwang'Ondiek et al 2021). As earlier explained, water drawdown in rice paddy induces carbon and nitrogen emissions from wetlands (Were et al 2019;Owino et al 2020), while fertilized rice paddies being hotspots for N2O emission (Owino et al 2020).…”
Section: Implication Of Rice Cultivation Permanent Flooding No Fertil...mentioning
confidence: 99%